Genetic variation at the 8q24.21 renal cancer susceptibility locus affects HIF binding to a MYC enhancer - Grampp, S; Platt, J; Lauer, V; Salama, R; Kranz, F; Neumann, V; Wach, S; Stöhr, C; Hartmann, A; Eckardt, K; Ratcliffe, P; Mole, D; et al. (Nature Publishing Group, 2016)
Clear cell renal cell carcinoma (ccRCC) is characterized by loss of function of the von Hippel-Lindau tumour suppressor (VHL) and unrestrained activation of hypoxia-inducible transcription factors (HIFs). Genetic and epigenetic determinants have an impact on HIF pathways. A recent genome-wide association study on renal cancer susceptibility identified single-nucleotide polymorphisms (SNPs) in an intergenic region located between the oncogenes MYC and PVT1. Here using assays of chromatin conformation, allele-specific chromatin immunoprecipitation and genome editing, we show that HIF binding to this regulatory element is necessary to trans-activate MYC and PVT1 expression specifically in cells of renal tubular origins. Moreover, we demonstrate that the risk-associated polymorphisms increase chromatin accessibility and activity as well as HIF binding to the enhancer. These findings provide further evidence that genetic variation at HIF-binding sites modulates the oncogenic transcriptional output of the VHL-HIF axis and provide a functional explanation for the disease-associated effects of SNPs in ccRCC.